Chapter Il museo della scuola come luogo di sperimentazione di percorsi di Public History: il caso del Museo della Scuola «Paolo e Ornella Ricca» dell'Università di Macerata - Brunelli, Marta (Studi e saggi, 2019)
Public historians have definitively recognized the crucial role that museums - on par with libraries, archives, schools as well as media, cultural and tourism industry, and «all other sectors where the knowledge of the past is required to work with different audiences» (AIPH, The Italian Public History Manifesto, 2018) - can play for the development of Public History practices. In this scenario, historians of education do well know the potential that is locked up inside the historical-educational museums too. A potential that, especially in university museums, can improve academic teaching quality, promote innovative research and, finally, foster cultural and social empowerment of communities.